PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SDN 011 BERINGIN MAKMUR KECAMATAN KERUMUTAN - Wijiati Wijiati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this research is the lack of students mathematics learning outcomes. This is because passive students in participating in learning, and in group learning activities, group less responsible members of the group, resulting in lower student learning outcomes. This study is a class action that aims to improve learning outcomes mathematics using cooperative learning model NHT. The research was conducted in classes VI SDN 011 Kerumutan Beringin Kecamatan Makmur. Research was conducted during two cycles. The research instrument consists of a sheet of teacher activity observation and student activity and learning outcomes. Based on the results of research and discussion, that the learning outcomes of students has increased after learning activities using cooperative learning model NH. This statement is supported by the results that have been raised previously, namely: (1) the results of the initial test results of learning mathematics students get an average of 54.00 with learning completeness percentage of 48%; (2) in the first cycle of students' mathematics learning outcomes increased with an average value of 64.00 with learning completeness percentage of 84%; and (3) in the second cycle students' mathematics learning outcomes increased with an average value of 67.00 with learning completeness percentage of 92%. This shows that the classical completeness has been reached, in which the research is successful if the completeness achieved 80% of students obtaining a minimum value of 70. Based on the results and discussion, it can be concluded that the application of cooperative learning model NHT can improve mathematics learning outcomes SDN 011 Beringin Makmur Kecamatan Kerumutan.